Qualitative literacy : a guide to evaluating ethnographic and interview research - Small, Mario Luis; Calarco, Jessica McCrory, 1983- (University of California Press, 2022)
"Suppose you were given two qualitative studies and were told that one of them is a piece of empirically sound social science and the other, though interesting and beautifully written, is not. What criteria would you use to tell the difference? Each of the hundreds of ethnographic and interview studies published yearly on inequality, poverty, education, public health, immigration, the family, criminal justice, and other social issues is scientifically either sound or unsound. This book provides a guide for social scientists, researchers, students, evaluators, policy makers, journalists and others seeking to better understand how to identify quality in field research"--